Pollution control enhanced spruce growth in the "Black Triangle" near the Czech-Polish border - Kolář, Tomáš; Čermák, Petr; Oulehle, Filip; Trnka, Miroslav; Štěpánek, Petr; Cudlín, Pavel; Hruška, Jakub; Büntgen, Ulf; Rybníček, Michal (The Science of the total environment, 2015)
Norway spruce (Picea abies (L.) Karst.) stands in certain areas of Central Europe have experienced substantial dieback since the 1970s. Understanding the reasons for this decline and reexamining the response of forests to acid deposition reduction remains challenging because of a lack of long and well-replicated tree-ring width chronologies. Here, spruce from a subalpine area heavily affected by acid deposition (from both sulfur and nitrogen compounds) is evaluated. Tree-ring width measurements from 98 trees between 1000 and 1350m above sea level (a.s.l.) reflected significant May-July temperature signals. Since the 1970s, acid deposition has reduced the growth-climate relationship. Efficient pollution control together with a warmer but not drier climate most likely caused the increased growth of spruce stands in this region, the so-called "Black Triangle," in the 1990s.
Keywords: Czechoslovakia; Environmental Monitoring; Picea; Air pollution; monitorování životního prostředí; Nitrogen; Poland; smrk; Sulfur; Air Pollution; Forest growth; Acid Rain; látky znečišťující vzduch; Central Europe; znečištění ovzduší; Československo; dusík; kyselý déšť; Polsko; Dendroecology; síra; Norway spruce; Air Pollutants